Maslahah base fatwa on issues relating to wealth in Malaysian contexts - Ibrahim, Badruddin; Mohd, Azizah (Serials Publication (P) Ltd, 2017)
Fatwa, in general, refers to a legal opinion on the legal ruling, which is issued by any Muslim jurist (mufti) relating to any particular issue that asked by the public. In principle, fatwa serves as a means of clarifying any issue that arises in Muslim society. The Muslim jurist has to rely on sources of Islamic law from the Qur’an, Sunnah, Ijma’, qiyas and other sources in his fatwa. One of the sources of Islamic law that becomes a basis of the fatwa is maslahah (public interest). Maslahah under Islamic Jurisprudence can be simply defined as ‘securing of benefit and interest to the human being and removing harm that might incur on them’. National Fatwa Committee on behalf of the state often issues the legal opinion (fatwa) in order to cope with the problem that arisen in the Muslim community. Issues normally involve personal affairs of the Muslim community, which include ruling relating to family matters, property law, succession law, wealth management, etc. This paper seeks to examine maslahah-based fatwa on issues relating wealth in the Malaysian context. For that purpose, a number of fatwa issued in Malaysia will be examined and analyzed as to whether such a fatwa is based on maslahah that is recognised and acceptable under the Shariah. The research will adopt qualitative research approach where analysis is done based on treatises of the Muslim jurist and the writings of the contemporary Muslims Scholars.